Поліпшення параметрів кремнієвих варикапів при використанні лазерного гетерування - Vikulin, I. M.; Litvinenko, V. N.; Shutov, S. V.; Maronchuk, A. I.; Demenskiy, A. N.; Glukhova, V. I. (PE "Politekhperiodika", Book and Journal Publishers, 2018)
The authors investigate how and why defects influence the inverse characteristics of varactors. The paper presents experimental results on the effect laser gettering has on the electrical parameters of varactors. The mechanisms of the laser gettering effect on the parameters of varactors are analyzed.